The flight of dragons : the fourth tale from the five kingdoms - French, Vivian (French, Vivian. Tale from the five kingdoms, 2011)
On Gracie Gillypot's birthday, greedy, chocolate-hungry twins awaken the banished Old Malignant One, and unless Gracie can find a powerful, long-forgotten dragon's egg, the Five Kingdoms may succumb to evil magic and Total Oblivion.